SEMANTIC STUDY OF NEOLOGISMS IN NEWSPAPER DISCOURSE OF ENGLISH AND UZBEK PUBLICATIONS - Mamadaliyeva Moxizarxon Tursinali qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to thestudy that the neologisms of the studied languageswere first studied in a theoretical aspect, a single definition of the concept of “neologism” in the language was developed, and the criteria for distinguishing between neologisms were characterized.